Development of transgenic tobacco plants carrying the cinnamyl alcohol dehydrogenase 1 gene of oil palm / Nur Afiqah Abdul Aziz - Abdul Aziz, Nur Afiqah (Faculty of Plantation and Agrotechnology, 2018)
Lignin is a phenolic heteropolymer in secondary cell walls that plays a main role in the development of plants and defence against any pathogens. The biosynthesis of monolignols, which represents the important component of lignin involves large amount enzymes. The Cinnamyl Alcohol Dehydrogenase (CAD) is a key enzyme in biosynthesis of lignin that catalyses the final step in the biosynthesis of monolignols. Based on previous sequence analysis, EgCAD1 is a bona fide CAD gene involves in lignin biosynthesis in oil palm. However, it is not supported by any scientific evidences. Functional study of the gene is required to prove the statement. Therefore, this study was performed to develop transgenic plants carrying the EgCAD1 gene from oil palm in order to provide materials for future functional study of the gene. Agrobacterium-mediated transformation method was applied in this research to transform the tobacco leaf discs. Shoots were regenerated from the Agrobacterium-infected leaf discs. Subsequently, the shoots were subcultured on rooting medium to induce root formation. Multiple lines of transgenic tobacco plants were produced through this study. The transgenic plants developed in this study will permit one to identify the functions of EgCAD1 gene in future.